Mental health and life satisfaction among nurses: a cross-sectional study. (1st June 2022) - Kchaou, A.; Abbes, A.; Hrairi, A.; Masmoudi, R.; Khrifech, F.; Hammami, K.; Masmoudi, M.L.; Masmoudi, J.; Hajjaji, M.
Abstract : Introduction: Nursing is highly demanding and stressful profession. Therefore, maintaining and improving psychological wellbeing among nurses seems essential to have a better life satisfaction and a better productivity. Objectives: The aim of this study was to assess the relationship between mental health and life satisfaction among nurses. Methods: The study was conducted in a group of active nurses from Hedi Chaker hospital in Sfax- Tunisia. Standardized questionnaires were used, including the general health questionnaire (GHQ-28) and the satisfaction with life scale (SWLS). Results: A total of 100 (males = 40; females = 60) nurses participated in this study. The mean age was 50.20 ±7.20 years. The average of job tenure was 25.25 ± 9.70 years. The majority of participants (66.7%) reported having chronic diseases. Rotating shifts work was noted in 72.50% of cases. Average scores for the GHQ-28 and the SWLS were respectively 30.66 ± 11.07 and 21.61± 6.23. The presence of chronic conditions was associated with psychological distress (higher GHQ-28 scores) (p = 0.01). Life satisfaction score was positively correlated with age (r= 0.29, p= 0.023), whereas it was negatively correlated with GHQ-28 scores (r= -0.36, p= 0.01). Low life satisfaction (SWLS scores between 5 and 14) was significantly associated with three domains of the GHQ-28: somatic symptoms (p = 0.008), anxiety (p = 0.001) and social dysfunction (p = 0.01). Conclusions: According to our study, low life satisfaction was associated with psychological disorder. Hence, nurses need support and subsequent interventions in order to improve psychological wellbeing and life-satisfaction. Disclosure: No significant relationships.